2023
DOI: 10.3390/rs15123044
|View full text |Cite
|
Sign up to set email alerts
|

Global Cloudiness and Cloud Top Information from AVHRR in the 42-Year CLARA-A3 Climate Data Record Covering the Period 1979–2020

Abstract: This paper investigates the quality of global cloud fraction and cloud-top height products provided by the third edition of the CM SAF cLoud, Albedo and surface RAdiation dataset from the AVHRR data (CLARA-A3) climate data record (CDR) produced by the EUMETSAT Climate Monitoring Satellite Application Facility (CM SAF). Compared with with CALIPSO–CALIOP cloud lidar data and six other cloud CDRs, including the predecessor CLARA-A2, CLARA-A3 has improved cloud detection, especially over ocean surfaces, and improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The differences between CN_WMO and Clim40 shown in Figures 1 and 3 for the total and low cloud fraction, respectively, are noteworthy. Previous studies have shown that the global cloud cover is generally decreasing when the trends are computed over the last forty years [21,23,25,26,48]. The decrease has mainly occurred over the sub-tropical to mid-latitudes in both hemispheres.…”
Section: Total and Low Cloud Fractionmentioning
confidence: 92%
See 2 more Smart Citations
“…The differences between CN_WMO and Clim40 shown in Figures 1 and 3 for the total and low cloud fraction, respectively, are noteworthy. Previous studies have shown that the global cloud cover is generally decreasing when the trends are computed over the last forty years [21,23,25,26,48]. The decrease has mainly occurred over the sub-tropical to mid-latitudes in both hemispheres.…”
Section: Total and Low Cloud Fractionmentioning
confidence: 92%
“…It employs cloud probabilistic detection based on the Naïve Bayesian theory, while the cloud top property algorithms employ artificial neural networks. A number of recent studies have documented the theoretical basis, validations, and improvements in the CLARA-A3 climate data record [21,26,[47][48][49].…”
Section: Satellite-based Cloud and Radiation Climate Data Recordmentioning
confidence: 99%
See 1 more Smart Citation
“…The subplots in these figures show biases against MODIS-Aqua and the fitted trends therein. All four CDRs show seasonality in the cloud amount biases against MODIS (Figure 1), which can be explained by the different detection sensitivity of these CDRs and the seasonal differences in the monsoonal systems and inter-tropical convergence zones between the two hemispheres (see [45,46] for further details). It is to be noted that all AVHRR based CDRs (i.e.…”
Section: A Global Overview Of Stabilitymentioning
confidence: 99%
“…All four CDRs show seasonality in the cloud amount biases against MODIS (Figure 1), which can be explained by the different detection sensitivity of these CDRs. The differences in detecting clouds over the monsoon regions, the inter-tropical convergence zone, and over the polar regions during respective polar winters can explain the observed seasonality in the biases (see [49,50] for further details). It is to be noted that all AVHRR-based CDRs (i.e., CLARA-A3, ESA Cloud CCI and PATMOS-x) satisfy even the strictest GCOS Goal requirements on the stability of derived cloud amounts.…”
Section: A Global Overview Of Stabilitymentioning
confidence: 99%